Treatment‐related mortality in newly diagnosed pediatric cancer: a population‐based analysis. (23rd February 2018) - Gibson, Paul; Pole, Jason D.; Lazor, Tanya; Johnston, Donna; Portwine, Carol; Silva, Mariana; Alexander, Sarah; Sung, Lillian; ,
Abstract: Using a previously developed reliable and valid treatment‐related mortality (TRM) definition, our objective was to describe the proportion of children newly diagnosed with cancer experiencing TRM and to identify risk factors for TRM in a population‐based cohort. We included children with cancer <19 years diagnosed and treated in Ontario who were diagnosed between 2003 and 2012. Children with cancer were identified using data in a provincial registry. Cumulative incidence of TRM was calculated where progressive disease death was considered a competing event. Among the 5179 children included, 179 had TRM, 478 died of progressive disease, and 4522 were still alive. At 5 years, the cumulative incidence of TRM among the entire cohort was 3.9% (95% confidence interval (CI) 3.3–4.5%). When compared to brain tumor patients, leukemia and lymphoma patients had a significantly higher risk of TRM (hazard ratio (HR) 2.5, 95% CI: 1.6–4.0; P  < 0.0001). Infants were at significantly higher risk of TRM across diagnostic groups. Other factors associated with higher risks of TRM were metastatic disease ( P  < 0.0001), diagnosis prior to 1 January 2008 ( P  = 0.001), hematopoietic stem cell transplantation (HSCT) ( P  < 0.0001), and relapse ( P  < 0.0001). The 5‐year cumulative incidence of TRM was 3.9% among newly diagnosed children with cancer. Infants were at higher risk of TRM across diagnostic groups. Other risk factors for TRM were leukemia or lymphoma, metastatic disease, earlier diagnosis year, HSCT, and relapse. Future work should further refine prognostic factors by specific cancer diagnosis to best understand when and how to intervene to improve outcomes. Abstract : Objective was to describe the proportion of children newly diagnosed with cancer experiencing treatment‐related mortality (TRM) and to identify risk factors for TRM in a population‐based cohort. When compared to brain tumor patients, leukemia and lymphoma patients had a significantly higher risk of TRM. Infants were at significantly higher risk of TRM across diagnostic groups.